1925
DOI: 10.1038/icb.1925.1
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Creatine in Muscular Contraction.

Abstract: INTRODUCTORY.It was in the investigations of Fick, carried out over fifty years ago, that the idea arose of two distinct chemical processes underlying the contraction and relaxation phases of a single muscle twitch. This conception, disregarded at the time, has during recent years been clearly established by the researches of Fletcher and Hopkins, of A. V. Hill, and of Meyerhof; and it is now quite certain that while contraction is caused by the liberation of lactic acid on to certain sensitive surfaces within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1927
1927
1993
1993

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…of phosphagen P. One might expect the muscle in situ to be in phosphate equilibrium with the blood. It has been known for some time that a muscle placed in Ringer's solution loses both phosphate(Embden &Adler, 1922) and creatine (Tiegs, 1925) faster in a fatigued than in a resting state, and an increase in the blood phosphate of athletes after a short spell of violent exertion has been recorded by Harvard & Reay (1926), while Embden & Grafe (1921) report that there is an increased excretion of phosphate by the kidney during the performance. All the evidence seems to point to a free diffusibility of phosphate through the cell wall.…”
Section: Creatine and Phosphagen Zn T'zvomentioning
confidence: 99%
“…of phosphagen P. One might expect the muscle in situ to be in phosphate equilibrium with the blood. It has been known for some time that a muscle placed in Ringer's solution loses both phosphate(Embden &Adler, 1922) and creatine (Tiegs, 1925) faster in a fatigued than in a resting state, and an increase in the blood phosphate of athletes after a short spell of violent exertion has been recorded by Harvard & Reay (1926), while Embden & Grafe (1921) report that there is an increased excretion of phosphate by the kidney during the performance. All the evidence seems to point to a free diffusibility of phosphate through the cell wall.…”
Section: Creatine and Phosphagen Zn T'zvomentioning
confidence: 99%
“…It has been shown that when the red-cell membrane is destroyed by haemolysis the liberated creatine is capable of passing through a semi-permeable membrane. Tiegs (1925) observed that although creatine can be dialysed from fatigued frog's muscle into saline it does not diffuse from resting muscle, which led him to suggest that creatine exists in muscle in two forms, one diffusible and the other non-diffusible. This speculation was confirmed by the discovery of Eggleton and Eggleton (1927) of a non-diffusible compound of creatine which Fiske and Subbarow (1929) identified as phosphocreatine.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding creatine no information has been published since the work of Tiegs [1925] who showed that creatine diffuses from fatigued frog muscles into a saline solution, but not from resting, and that the admission of oxygen diminished diffusibility. He rightly supposed that creatine must exist in two forms in the muscle, the diffusible form predominating in the fatigued state.…”
mentioning
confidence: 99%